2015
DOI: 10.1158/1535-7163.mct-15-0069
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Protein 90 Is a Potential Therapeutic Target in Cholangiocarcinoma

Abstract: Cholangiocarcinoma is an aggressive malignancy with a poor prognosis, with no effective therapy other than surgical resection. Heat shock protein 90 (HSP90) is a key component of a multichaperone complex involved in the posttranslational folding of a number of client proteins, many of which play essential roles in tumorigenesis. Here, we attempted to clarify its prognostic significance and potential utility as a therapeutic target in cholangiocarcinoma. Immunohistochemical expression of HSP90 was assessed retr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…HSP90 family consists of five members that are encoded by the HSPC1-5 genes which modulate tumor growth, adhesion, invasion, metastasis, angiogenesis, and apoptosis [51]. Many studies have reported that HSP90 is often overexpressed and associated with poor prognosis in multiple tumors, including cholangiocarcinoma, lung, gastric, and breast cancers and glioblastoma [8,[66][67][68][69]. The increased expression of HSP90 promotes carcinogenesis through regulation of correct folding, stability, and function of numerous oncogenic proteins.…”
Section: Role Of Hsp90 In Cancer Developmentmentioning
confidence: 99%
“…HSP90 family consists of five members that are encoded by the HSPC1-5 genes which modulate tumor growth, adhesion, invasion, metastasis, angiogenesis, and apoptosis [51]. Many studies have reported that HSP90 is often overexpressed and associated with poor prognosis in multiple tumors, including cholangiocarcinoma, lung, gastric, and breast cancers and glioblastoma [8,[66][67][68][69]. The increased expression of HSP90 promotes carcinogenesis through regulation of correct folding, stability, and function of numerous oncogenic proteins.…”
Section: Role Of Hsp90 In Cancer Developmentmentioning
confidence: 99%
“…Some of our established cell lines were found to be resistant to gemcitabine (Table 2), thereby allowing highly practical preclinical studies to be conducted. In addition, we conducted molecular pathology analyses of cell lines and constructed a clinical pathological database of patients undergoing BTC resection to establish appropriate parameters for drug efficacy studies to explore new biomarkers for practical applications (Figure 1)[2-5]. All experiments were approved by the Animal Care and Ethics Committee of the National Cancer Center (ID: T05-046).…”
Section: To the Editormentioning
confidence: 99%
“…Combining therapies that inhibit different intracellular signaling pathways have the potential to be more effective than inhibition of a single pathway and overcoming tumor resistance. A new promise in gallbladder treatment is the inhibition of the master heat shock protein 90, a protein that in the last decade has emerged as an exciting target for cancer therapy, which is a master regulator of the stability and activity of multiple oncoproteins such as p53, HER-2, Akt, Bcr-Abl, c-Kit, EGFR and mutant BRAF [24]. Thus, our study assesses the expression of two major genes involved in the pathogenesis of GBC, correlates it with clinicopathological parameters and establishes it as an independent prognostic factor in GBC.…”
Section: Discussionmentioning
confidence: 99%